Transformasi Pembelajaran Digital melalui Platform Thunkable bagi Siswa di SMA Negeri 2 Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Irwan Soulisa; Christen Christen; Giovani Giovani; Foni Foni (Lembaga Pengembangan Kinerja Dosen, 2025)
The transformation of education in the digital era demands inclusive, creative, and relevant learning innovations in line with technological developments. To address these challenges, utilizing digital platforms is a strategic step in driving the digitalization of education. One innovative solution that is becoming widely used is no-code platforms like Thunkable, which enable users, including students, to create applications without having to master complex programming. This article reviews the results of a community service activity conducted at SMA Negeri 2 Sorong City, focusing on improving digital literacy and strengthening 21st-century skills through training in creating educational applications based on Thunkable. This activity utilized experiential learning and project-based learning approaches, implemented through hands-on training, interactive demonstrations, independent practice, and participatory evaluation. This training not only targeted students as the primary participants but also involved teachers as facilitators who accompanied the learning process and encouraged the application of training outcomes in classroom activities. Evaluation results showed a significant increase in student enthusiasm, critical thinking skills, and creativity in designing simple educational applications tailored to learning needs and local contexts. Despite obstacles such as limited digital devices and uneven internet access, this activity still succeeded in creating an innovative and transformative learning space. Furthermore, this training makes a significant contribution to supporting the implementation of the Pancasila Student Profile, particularly in the areas of digital literacy, independence, mutual cooperation, and creativity. It also serves as an effective means to instill the value of digital responsibility and foster a learning culture that is adaptive to technological change. The success of this program demonstrates that a simple yet applicable technology-based approach like Thunkable can be replicated in other schools, particularly in the 3T (disadvantaged, frontier, and outermost) regions, with the support of structured and collaborative training.